Implementasi Prinsip-Prinsip Good Governance di Kantor Dinas Kependudukan Dan Pencatatan Sipil Kota Tangerang Selatan - Hana Hana; Abdul Rahman (Student Scientific Creativity Journal, 2024)
The South Tangerang Civil Registration Population Service has the task of providing community service by applying the principles of Good Governance. In its implementation, several problems are still found, such as a system that is often down and employee responsiveness which is part of accountability and there is still discrimination in services which is part of legal violations of rights. Same. This research aims to find out how the principles of Good Governance are implemented in the Population and Civil Registry Office in South Tangerang City. The method used is descriptive with a qualitative approach in data collection techniques in the form of interviews, observation and documentation. The results of this research are, 1. Accountability has carried out accountability every day, and each division has carried out accountability through reporting to the head of service where the results of the report usually contain sanctions for employees who are negligent in their duties, and the competencies possessed by the employees. And it is necessary to involve community participation to monitor the performance of the institution, 2. Transparency has been carried out well by the institution but there needs to be increased training and awareness of employees, 3. Participation has been carried out well by the institution but there needs to be training related to digital literacy involving the community and figures community, and creating inclusive forums in order to create good public services and in accordance with the principles of good governance, 4. The rule of law is not yet running well because there are still acts of discrimination by differentiating services between someone who has a position and one who does not have a position, so it is necessary to law enforcement that is applied fairly and inclusively regardless of a person's social status and training through education in schools.